RESEARCH PROJECT: Early Literacy Development (2018)
This Project emerges in a private school in Bogotá. It is a description about the early literacy development in L2 in preschool. For this particular project the description is focused on the way students from 4 to 6 years old are approached to the development of English literacy through centers. The study takes place in a private school located in Bogotá, with students from kinder 4, kinder 5 and transition. The school´s name is CIEDI. It is located in km3 Suba Cota in Bogotá. Founded in 1977 CIEDI Became bilingual in 2000 and started to belong to the International Baccalaureate Organization (IB) in 2006. The school offers English as language A or B and French as language B. English is the language of instruction in the school, and it is phonics based in the preschool level, for this reason it is important for the school to provide opportunities for the students to understand and use English daily and meaningfully.